Electronic health record patient portal adoption by health care consumers - Tavares, Jorge (2017)
Tavares, J., & Oliveira, T. (2016). Electronic health record patient portal adoption by health care consumers: An acceptance model and survey. Journal Of Medical Internet Research, 18(3), [e49]. https://doi.org/10.2196/jmir.5069